Efek Bentonit pada Karakteristik Pembakaran Droplet Biodiesel Kelapa Sawit - Wijayanto, Vera Dwi; Hamidi, Nurkholis; Wijayanti, Widya (Jurnal Rekayasa Mesin, 2020)
The blends of fuel to base liquid fuels for the enhancement of combustion properties has long generated interest since it is linked to improvement in combustion properties in biodiesel fuels. This work investigates the effect of bentonite nanoparticles on the combustion characteristics of palm oil biodiesel. These nanoparticles are added in various compositions on biodiesel which are 0% (B0), 10% (B10), 20% (B20) and 30% (B30). The insulin pen was used to make Sub-millimeter-sized spherical droplets, and the combustion process of droplets was recorded using a camera in atmosphere condition. The fuel was dripped on the tip of the thermocouple junction and ignited using a torch of the butane-air mixture on a cylindrical burner. Properties such as ignition delay, burning rate, and flame temperature of droplets were measured with post-processing of the resulting images. The results showed a decrease in ignition delay and an increase of flame temperature with the increase of bentonite percentage due to bentonite acts as a catalyst capable of accelerating the reaction rate. However, the burning rate decrease with the increasing of bentonite percentage due to the oxygen content of the mixture is getting lower.